Leader Development in Army Units Views from the Field - Schirmer, Peter (RAND Corporation, 2008)
Summarizes discussions with over 450 Army officers (lieutenants through colonels) about leader development in Army units. These discussions revealed that the type and extent of leader development activities vary greatly across units, but that they are generally informal and most heavily influenced by the unit commander. The authors conclude with suggestions on how the Army school system can improve leader development.